Extension: digital audio technology in Papua New Guinea - Olsson, Micael; Bell, Douglas (Technical Centre for Agricultural and Rural Cooperation, 2005)
Micael Olsson and Douglas Bell describe how digital audio technology is helping to promote traditional culture as the basis for forest resource management.